Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Stres Kerja Sebagai Variabel Intervening Pada Dinas Tenaga Kerja Dan Transmigrasi Provinsi Sumatera Barat - Anggi Trimarliani Saputri; Ramdani Bayu Putra; Nila Pratiwi (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of workload and work environment on employee performance through work stress as an intervening variable at the Manpower and Transmigration Office of West Sumatra Province. The method used in this study is a quantitative approach with data collection techniques through questionnaires that have been tested for validity and reliability. Partial Least Square (PLS) is used to test the hypothesis in this study using SmartPLS 3.0. The sample of this study involved 60 respondents who were randomly selected from the agency. The results of the study indicate that there is a positive and significant effect of workload on work stress. There is a positive and significant effect of work environment on work stress. There is a positive and significant effect of workload on employee performance. There is a positive and insignificant effect of work environment on employee performance. There is a positive and insignificant effect of work stress on employee performance. There is a positive and insignificant effect of workload on employee performance through work stress. There is a positive and insignificant effect of work environment on employee performance through work stress..